2001
DOI: 10.1212/wnl.56.11.1565
|View full text |Cite
|
Sign up to set email alerts
|

Local vs systemic corticosteroids in the treatment of carpal tunnel syndrome

Abstract: The authors compared the effectiveness of low-dose, short-term oral prednisolone vs local methylprednisolone injection in a prospective, double-blinded, parallel treatment study of carpal tunnel syndrome (CTS). A single injection of 15 mg methylprednisolone resulted in significant improvement in global symptom scores over a 12-week period. This study demonstrated the superiority of local steroid injection to oral steroid in the treatment of CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 11 publications
2
46
0
7
Order By: Relevance
“…This percentage is identical to the results of Dammers and colleagues (1999), who reported improvement in 77% 1 month after treatment. Although some investigators have reported slightly lower percentages of success, there is no doubt about the beneficial shortterm effect of corticosteroid injections (Armstrong et al, 2004;Bickel, 2010;Bland, 2007;Girlanda et al, 1993;Hagebeuk and de Weerd, 2004;Herskovitz et al, 1995;Marshall et al, 2009;Peters-Veluthamaningal et al, 2010;Wong et al, 2001). Similar to our results, in the study by Dammers et al (1999) a good outcome decreased from 77% after 1 month to 39% after 1 year of follow-up.…”
supporting
confidence: 88%
“…This percentage is identical to the results of Dammers and colleagues (1999), who reported improvement in 77% 1 month after treatment. Although some investigators have reported slightly lower percentages of success, there is no doubt about the beneficial shortterm effect of corticosteroid injections (Armstrong et al, 2004;Bickel, 2010;Bland, 2007;Girlanda et al, 1993;Hagebeuk and de Weerd, 2004;Herskovitz et al, 1995;Marshall et al, 2009;Peters-Veluthamaningal et al, 2010;Wong et al, 2001). Similar to our results, in the study by Dammers et al (1999) a good outcome decreased from 77% after 1 month to 39% after 1 year of follow-up.…”
supporting
confidence: 88%
“…They found that injections produced better results in the study group. 7 O'Gradaigh et al compared low-and high-dose and short-and long-acting corticosteroids in the treatment of CTS and found that low-dose corticosteroid is as effective as higher doses and potentially less toxic in short-and long-term followup. 8 We used six mg of betamethasone for injections and believe this dose is effective, but in our study we did not compare different doses in the different groups.…”
Section: Discussionmentioning
confidence: 99%
“…In seven studies of adequate methodology 6,7,8,9,10,11,12,13 , Piazzini et al 11 concluded that corticosteroid injection in the carpal tunnel can be considered as an effective treatment. However, no significant clinical benefit was found for corticosteroid injections compared with other treatments, including splint immobilization 14,15 .…”
Section: Corticosteroid Injectionmentioning
confidence: 99%